Optimizing the Implementation of Waqf within the Framework of National Law and Sharia - Warman, Syafil; Muhlizar (IJCS: International Journal of Community Service, 2024)
Waqf is a philanthropic institution in Islam that has been the subject of has been the subject of debates on Islamic law since classical times to the modern era. The topics of discussion include the existence of the waqif, mauquf ‘alaih (nadzir), mauquf (object), and sighat (proclamation). Fiqh and Indonesian law, referred to as UU (Act), have given significant attention and analysis to these topics. The latest efforts have focused on combining and accommodating these laws to reconstruct and expand the implementation scope of waqf. The philanthropic objective of the organization is to achieve public welfare through reinterpretation of its earliest concept. This paper will also discuss emerging issues such as cash waqf (waqf al-nuqud) and productive waqf, which have arisen due to lack of professionalism and mismanagement of waqf objects. These elaborations aim to analyze the content substance of Act 41/2004 as a compromised solution conducted by the Rule.